Impregnation of clove extract (Eugenia Caryophyllus) in polycarbonate and poly(l-lactic acid) via supercritical co2 - Jordão, Amanda Martins (2022)
Coordenação de Aperfeiçoamento de Pessoal de Nivel Superior